A Comparative Study of English-Arabic-English Translation Constraints among EFL Students - Akki, Fouad; Larouz, Mohammed (International Journal of Linguistics and Translation Studies, 2021)
Because most of the previous research on translation constraints in English-Arabic-English translation has separately investigated English-Arabic and Arabic-English translation problems, the current study is meant to compare the constraints that EFL students face across the two translation types. To attain this objective, English-Arabic and Arabic-English tests were administered to forty-seven (N= 47) EFL students in two Moroccan university educational settings to measure their abilities in the two translation domains. The results reveal that the participants' scores in both versions are not at the expected ability level due to the obstacles they encounter in the translation process. The study also shows that having a good ability in the English-Arabic version cannot strongly predict a similar good ability in Arabic-English translation because of the different natures of the two languages, which suggests taking more care of the student’s proficiency in English and Arabic languages and exposing students to their distinctive aspects for the sake of coming up with accurate and appropriate translations. The study ends with implications for pedagogy and recommendations for future researchers.